E-LEARNING LEARNING USING THE GOOGLE CLASS ROOM APPLICATION IN PRIMARY SCHOOLS (SD) - Dalimawaty Kadir; Ika Sartika; Agus Makmur (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2021)
This development research aims to develop e-learning media using the google class room application for grade V elementary schools. The method used in this study is research development (Research and Development). This research was conducted at SD Dahrul Hikmah. The method used in data collection is a questionnaire.The results of this research and development were carried out in several stages which were adapted from the ADDIE version of the development research model. The stages are: Analysis, Design, Development, and Implementation. The analysis stage includes field studies and literature studies. The design stage includes making e-learning. The development stage includes the creation of a google class room. The implementation stage is carried out in two cycles, namely small group product trials involving 4 students and large group product trials involving 27 students. The results of the trials on students got an average score of 4.6 with the very good category. Thus the e-learning media using the google class room application is feasible to be used as a learning medium for grade V SD.